1993
DOI: 10.1007/bf01324560
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of bystander intervention variables to adolescents' responses to suicidal peers

Abstract: This study sought to understand factors that might enhance su&ide prevention programs by investigating the responses of adolescents to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 14 publications
3
36
1
3
Order By: Relevance
“…Many research topics that have applied the use of vignettes -pain (Bendelow 1993), suicide (Kalafat et al 1993, Kalafat andGagliano 1995), sexual standards (Bettor et al 1995), relationship violence (Carlson 1996), rape (Furnham and Boston 1996), drug injecting (McKeganey et al , 1996 and deviance (Kirmayer et al 1997) -are arguably regarded as 'sensitive' (Lee 1993) or 'unrespectable' (Dean and Barrett 1996) research topics. Vignettes provide a useful way in to discussing these issues and also as a means of introducing personal experiences.…”
Section: The Differences Between Real Life and Vignette Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many research topics that have applied the use of vignettes -pain (Bendelow 1993), suicide (Kalafat et al 1993, Kalafat andGagliano 1995), sexual standards (Bettor et al 1995), relationship violence (Carlson 1996), rape (Furnham and Boston 1996), drug injecting (McKeganey et al , 1996 and deviance (Kirmayer et al 1997) -are arguably regarded as 'sensitive' (Lee 1993) or 'unrespectable' (Dean and Barrett 1996) research topics. Vignettes provide a useful way in to discussing these issues and also as a means of introducing personal experiences.…”
Section: The Differences Between Real Life and Vignette Responsesmentioning
confidence: 99%
“…While others may see themselves as different from other people and likely to respond in different ways. For example, the study by Kalafat et al (1993) on suicidal peers found that the majority of students would talk to the person or tell an adult and most reported that they would act in the same way. However, their results do show a sizeable minority of students who found that other students would do nothing or ignore the suicidal student in the vignette situations.…”
Section: The Differences Between Real Life and Vignette Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…• Education and training of individuals: providing education and training for students [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] , increasing self efficacy among students 35) • Development of a support network: Development a support network among students 23,36,37) • Cooperation from internal and external resources:…”
Section: Schoolmentioning
confidence: 99%
“…When young adults experience high levels of stress and depression, which place them at increased risk for suicide, their peer group may be the most effective in recognizing suicidal symptoms and taking steps to assist the at-risk peers (e.g., Kalafat, Elias, & Gara, 1993;Schepp & Biocca,1991). Such assistance may take a variety of forms including both affective (e.g., sympathy, companionship) and instrumental (e.g., problem solving, referral) types of support (Cramer, 1990;Folkman & Lazarus, 1985).…”
mentioning
confidence: 99%